The Role of the Adults’ Educator in Teacher Training Programs - Tzovla, Eirini; Kedraka, Katerina (American Journal of Education and Learning, 2020)
The adult educators must acquire formal and substantive qualifications and develop skills that contribute to achieving the best learning outcomes. This paper dealt with the role of the adults’ educator in teacher training programs.The role of the teacher training programs is to enhance an educational relationship, based on equity, between the teacher and the learner, with respect to the learners' needs and treatment as mature personalities with independent expertise. This research intended to investigate whether adult education methods are applied in teacher training programs and to describe the profile of the adult educator. The paper used the qualitative method. The major research results highlighted teachers believe that the adult educator plays a paramount role in their training and they insist that he must have good knowledge of adult education, experience as a trainer, and respect for his learners, empathy, and tolerance and he must also understand the special features of the adult learners.